Specialization to cold‐water upwellings may facilitate gene flow in seabirds: new evidence from the Peruvian pelican Pelecanus thagus (Pelecaniformes: Pelecanidae). (30th January 2013) - Jeyasingham, Will S.; Taylor, Scott A.; Zavalaga, Carlos B.; Simeone, Alejandro; Friesen, Vicki L.
<x xml:space="preserve">Abstract</x> Recent research has shown that tropical seabirds specialized to feed on cold water upwellings exhibit low population genetic differentiation and high gene flow across large geographic distances. This pattern is opposite to the general pattern of differentiation reported for tropical seabirds, and led us to hypothesize that specialization to cold‐water upwellings facilitates gene flow between colonies. As a test of this hypothesis we characterized population differentiation and gene flow across the range of the Peruvian pelican Pelecanus thagus, an upwelling specialist endemic to the Humboldt Current, using an 838 base pair segment of the mitochondrial control region and seven microsatellite loci. In support of our hypothesis we report genetic panmixia across the geographic range of this species and inferred high gene flow between colonies. The high dispersal propensity of upwelling specialist seabirds (adults and/or juveniles) may reduce loss of genetic diversity during population declines, and increase the ability of these species to colonize new islands.